International images in Alisher Navoi's poetry - Toshquvatova Mashhura Aktam qizi (Peerian Journals Publishing, 2022)
This article is devoted to the study of international images in the works of Alisher Navoi. Alisher Navoi, one of the many writers in the classical literature of the East, included in his poetry symbols that are understandable to all. With the help of these images, he helped to reveal the essence of the content of his poems. We can see this only in the example of the prophet Khidr. In addition, the skillful use of folk proverbs can be a proof of our opinion.
Keywords: commonality; psyche; folklore images; art